2022
DOI: 10.1186/s13058-022-01518-y
|View full text |Cite
|
Sign up to set email alerts
|

Population-based estimates of age-specific cumulative risk of breast cancer for pathogenic variants in ATM

Abstract: Background Multigene panel tests for breast cancer predisposition routinely include ATM as it is now a well-established breast cancer predisposition gene. Methods We included ATM in a multigene panel test applied to the Australian Breast Cancer Family Registry (ABCFR), a population-based case–control–family study of breast cancer, with the purpose of estimating the prevalence and penetrance of heterozygous ATM pathogenic variants from the family da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…ATM gene is an established breast cancer susceptibility gene, generally placed in the moderate‐risk category with a combined estimation of 2‐fold risk for the predisposing alleles. The estimated lifetime breast cancer risk varies in different studies from 13% to 33% by the age of 80 years 15,23‐25 . According to the ClinVar database, up to 1500 PVs have been reported in the ATM gene in the context of A‐T syndrome and/or hereditary cancer‐predisposing syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATM gene is an established breast cancer susceptibility gene, generally placed in the moderate‐risk category with a combined estimation of 2‐fold risk for the predisposing alleles. The estimated lifetime breast cancer risk varies in different studies from 13% to 33% by the age of 80 years 15,23‐25 . According to the ClinVar database, up to 1500 PVs have been reported in the ATM gene in the context of A‐T syndrome and/or hereditary cancer‐predisposing syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated lifetime breast cancer risk varies in different studies from 13% to 33% by the age of 80 years. 15 , 23 , 24 , 25 According to the ClinVar database, up to 1500 PVs have been reported in the ATM gene in the context of A‐T syndrome and/or hereditary cancer‐predisposing syndrome. Previous studies have suggested that the breast cancer risk is higher for carriers of an ATM loss‐of‐function variants than it is for carriers of an ATM deleterious missense variants (MVs).…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous pathogenic variant in ATM is associated with a 13-33% cumulative lifetime risk for breast cancer ( 83 , 84 ). Risk-reducing mastectomy is not recommended for carriers; however, it might be considered based on personal and family history.…”
Section: Moderate Penetrance Genesmentioning
confidence: 99%